Nanomapping and speciation of C and Ca in thermally treated lignocellulosic cell walls using scanning transmission X-ray microscopy and K-edge XANES. (1st March 2016) - Thyrel, Mikael; Backman, Rainer; Thånell, Karina; Karunakaran, Chithra; Skyllberg, Ulf; Lestander, Torbjörn A.
Highlights: STXM NEXAFS enabled study of RCG cell wall breakdown following thermal treatment at 90–500 °C. Thermal treatments at 300 °C induced small changes in RCG cell walls, indicating recalcitrance. At 400 and 500 °C more pronounced changes were observed indicating thermal decomposition. Ca nanomapping revealed a particle size distribution shifted to ultrafine sizes (<200 nm). Abstract: The carbon matrix in cell walls of lignocellulosic plants has high recalcitrance to chemical and biological decomposition. Thermal treatments, such as torrefaction and pyrolysis are therefore of interest to pre-process biomass. Reed canary grass (RCG) as biomass model was treated at 90, 300, 400 and 500 °C in N2 atmosphere. The induced cell wall changes, especially for C and Ca and their speciation and nanomapping were studied using synchrotron based (1) scanning transmission X-ray microscopy (STXM) C 1s near edge X-ray absorption fine structure (NEXAFS) spectroscopy, (2) STXM Ca K-edge NEXAFS, and (3) Ca K-edge X-ray absorption of near edge structure (XANES) spectroscopy. Clusters of nano-based pixels having different spectral features were identified using principal component analysis of mosaics of C 1s NEXAFS images. At 300 °C there were only minor changes and peaks related to lignin were only slight reduced. At 400 °C, the chemical change was substantial and most resonances related to CO and CH functional groups declined considerably. Finally, at 500 °C there were two clusters indicating that the structural integrity of the cell wall was lost and aromatic CC resonances related to quinones appeared. These results were confirmed by FT-IR. The nanomapping also indicated that Ca oxalate has a sub-micron particle size distribution, most sizes <200 nm. These may act as seed particles during combustion. Ca speciation according to Ca K-edge XANES showed that oxalate (CaC2 O4 ) was the primary phase of Ca and thermal treatment induced minor Ca phase transition into butschliite (K2 Ca(CO3 )2 ) and hydroxyapatite (Ca5 (PO4 )3 OH).